Uwarunkowania konkurencyjności produktów regionalnych w ofercie artykułów spożywczych - Jąder, Karolina (The Conditions of Regional Products Competitiveness in the Offer of Food Products, 2006)
The aim of this paper is to describe the conditions of the regional products competitiveness in the offer of the selected food products groups. The food products market of Wielkopolska - the intentionally selected region - is the object of this research. The competitiveness of the regional products from Wielkopolska in comparison to the food products from the other regions of Poland are analyzed. The outcomes of the consumers surveys are the base of this comparison. The surveys were made among the citizens of Poznan - the largest city in the Wielkopolska. The conditions and possibility of increasing the sale of the regional products in the analyzed region are analyzed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 341-347